Managing price risks in India's liberalized agriculture can future markets help? - World Bank (Washington World Bank, 1999)
This report will cover agricultural trade and price policies in the South Asia, examining the implications of the Uruguay Round on South Asia's agriculture and in the case of India. The perfomance of selected agricultural commodity markets and of water ma
Keywords: Commodity exchanges-India; Commodity futures-India; Agricultural prices-India; Agriculture and state-India